Market power and merger simulation in retail banking - József Molnár (Bank of Finland, 2008)
This paper tests market power in the banking industry. Price-cost margins predicted by different oligopoly models are calculated using discrete-choice demand estimates of own-price and cross-price elasticities. These predicted price-cost margins are then compared with price-cost margins computed using observed interest rates and estimates of marginal costs. This paper This among the first to. apply this methodology on a detailed, bank-level dataset from the retail banking sector. It extends on previous papers and illustrates the advantages of structural modelling by simulating a counterfactual merger experiment with a number of mergers, each of which involves two major banks, and studying the unilateral effect of the mergers on interest rates. This provides more evidence that concentration measures (such as the Herfindahl index) could be very misleading indicators of market power.
URN:NBN:fi:bof-20140807450
Keywords: G21; L11; L13; 330; demand; discrete choice; product differentiation; banking; market power; merger simulation